A clinically relevant in vivo model for the assessment of scaffold efficacy in abdominal wall reconstruction. (30th December 2016) - Chan, Jeffrey CY; Burugapalli, Krishna; Huang, Yi-Shiang; Kelly, John L; Pandit, Abhay
An animal model that allows for assessment of the degree of stretching or contraction of the implant area and the in vivo degradation properties of biological meshes is required to evaluate their performance in vivo. Adult New Zealand rabbits underwent full thickness subtotal unilateral rectus abdominis muscle excision and were reconstructed with the non-biodegradable Peri-Guard ®, Prolene ® or biodegradable Surgisis ® meshes. Following 8 weeks of recovery, the anterior abdominal wall tissue samples were collected for measurement of the implant dimensions. The Peri-Guard and Prolene meshes showed a slight and obvious shrinkage, respectively, whereas the Surgisis mesh showed stretching, resulting in hernia formation. Surgisis meshes showed in vivo biodegradation and increased collagen formation. This surgical rabbit model for abdominal wall defects is advantageous for evaluating the in vivo behaviour of surgical meshes. Implant area stretching and shrinkage were detected corresponding to mesh properties, and histological analysis and stereological methods supported these findings.